Perceptions of Traditional Dayah Z Generation Towards Aceh Heroines and Gender Equality Awareness - Khatimah, Husnul; Astuti, Fuji; Saptiani, Saptiani (SAINTIS Publishing, 2024)
In This study, the researchers delved into this based on the Z generation in Traditional Dayah through a case study of Three Dayah in Three districts in Aceh. The researchers figured out whether they perceived the same beliefs as their elder scholars. What did they think about their Acehnese Heroines’ contribution and struggle? To investigate balanced data, a purposive sampling method was applied to choose one female and one male student from each Dayah: six participants in total. The participants were interviewed one by one and added voice notes usage to facilitate their sensitive thoughts. The data was analyzed using thematic analysis. Nevertheless, the perception of all participants was not fully categorized into one fix terminology as they did not tend to agree to all characteristic in one terminology. Of six participants, 3 participants had a more conservative perception but two of them did not agree on second characteristic of conservative, two others were fully progressive as they agreed to all characteristics of progressive. Lastly, only one shared “almost moderate” one, even though she strongly argued about the first characteristic of moderate. In the same time, all of them have a positive perception of the Acehnese heroines, even though three of them were doubtful about “the appearance of the heroines whose hairs were unveiled.” Even though they shared the same educational background in traditional Dayah, the perception and daily practice of their family also strongly influenced their perception.